2003
DOI: 10.1167/iovs.02-0464
|View full text |Cite
|
Sign up to set email alerts
|

HSV1 Latency Sites after Inoculation in the Lip: Assessment of their Localization and Connections to the Eye

Abstract: After inoculation into the upper lip of mice, HSV1 established latency in several nervous system structures that have direct or indirect connections with ocular tissues. These results suggest that after an oral primary infection, the most frequent in humans, HSV1 may establish latency in several sites connected to the eye and may finally result in herpetic ocular disease involving the cornea, the iris, or even the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…These results are in agreement with the observation that HSV-1 latency in humans occurs within the TG, the central, and the autonomic nervous pathways, including the SCG (21,21,23,45,82). However, we observed larger numbers of neurons expressing LATs in the TG than in the other latently infected structures despite a similar level of productive infection (39). These data suggested that fundamentally different patterns of HSV-1 latency may occur in distinct neuronal cell types.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…These results are in agreement with the observation that HSV-1 latency in humans occurs within the TG, the central, and the autonomic nervous pathways, including the SCG (21,21,23,45,82). However, we observed larger numbers of neurons expressing LATs in the TG than in the other latently infected structures despite a similar level of productive infection (39). These data suggested that fundamentally different patterns of HSV-1 latency may occur in distinct neuronal cell types.…”
supporting
confidence: 92%
“…Wild-type HSV-1 strain SC16 (30) and the recombinant strain SC16 110LacZ (41), which contains an ICP0 promoter-driven lacZ inserted into the nonessential US5 gene of HSV-1, were used. Viruses were propagated and titrated as previously described (37)(38)(39).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations